1978
DOI: 10.3758/bf03197461
|View full text |Cite
|
Sign up to set email alerts
|

On interpretation of interactions

Abstract: The principle focus of this paper is on interpretation of interactions that are obtained when response probability is used as a dependent variable. It is argued that results obtained with probability (or any dependent variable) are only interesting insofar~s they reflect something about a corresponding theoretical component. It follows that the functional mapping of response probability (which is measured) onto the state of a theoretical component (which is inferred) must be somehow specified if conclusions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
338
1
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(346 citation statements)
references
References 8 publications
3
338
1
4
Order By: Relevance
“…Although linearity may bear an approximation to some actual psychological relations, many other such relations are decidedly nonlinear, which means that investigating them within the context of linear theory produces profoundly misleading results. A classic example of this problem involves interpretations of interactions (see, e.g., Bogartz, 1976;Loftus, 1978Loftus, , 1985Loftus & Bamber, 1990): As interpreted within the context of linear theory, nonordinal interactions observed with one dependent variable (e.g., recognition performance) can disappear or reverse with another dependent variable (e.g., dЈ) or a theoretical construct (e.g., "memory strength") that is monotonically but nonlinearly related to the dependent variable.…”
Section: Linear Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although linearity may bear an approximation to some actual psychological relations, many other such relations are decidedly nonlinear, which means that investigating them within the context of linear theory produces profoundly misleading results. A classic example of this problem involves interpretations of interactions (see, e.g., Bogartz, 1976;Loftus, 1978Loftus, , 1985Loftus & Bamber, 1990): As interpreted within the context of linear theory, nonordinal interactions observed with one dependent variable (e.g., recognition performance) can disappear or reverse with another dependent variable (e.g., dЈ) or a theoretical construct (e.g., "memory strength") that is monotonically but nonlinearly related to the dependent variable.…”
Section: Linear Theorymentioning
confidence: 99%
“…It was to solve this problem that in Simulations 2 and 3, we devised the linear structure in terms of "Strength," and then transformed Strength to probability via a nonlinear (Gaussian) mapping. The consequences of such nonlinearities have been discussed in the literature (see Loftus, 1978) and can lead to all manner of illusion and inconsistency, particularly when interpretation of interactions are at issue. The inconsistencies, apparent over iterations in all simulations when analyzed within the context of a linear theory, are simply examples of this general problem.…”
Section: The Unnatural Nature Of a Linear Structurementioning
confidence: 99%
“…It is worth pointing out that there is clearly no interaction between age and condition, in spite of this age effect on the number of items: the age difference is not larger in the alphabetical condition than in the direct condition. However, the presence ofa group effect is a problem, because it is still possible that an interaction would come out in a transformed version of the data (Loftus, 1978). In principle, this group effect should not have been found, because the subjects were tested with sequen~e lengths that corresponded to their spans as measured .m t~e preexperimental phase.…”
Section: Subjectsmentioning
confidence: 99%
“…A passive storage deficit in elderly people might thus be responsible for their observed difficulties in manipulating information, as it makes them particularly sensitive to tasks requiring both the retention and the manipulation of information. Loftus (1978) has pointed out the complexities of interpreting interaction effects in memory research, because the shape of the function that relates response probability to a particular theoretical component is generally unspecified. Salthouse (1985) has raised the same concerns in aging research, mentioning that the frequently observed baseline differences between young and elderly subjects is a serious problem when examining interaction effects.…”
Section: Manipulation In Normal Aging 573mentioning
confidence: 99%
“…Thus, they discuss the problem of the shape of the underlying distribution in interpreting interactions as if this concerned specifically single-patient methodology. This is simply an error (see Loftus, 1978;Pachella, 1974). The other confusion they add concerns the problem of "base rates and expected values."…”
mentioning
confidence: 99%